TOURISM VILLAGE DEVELOPMENT STRATEGY PEMATANG JOHAR, DELI SERDANG REGENCY - Lestari Situmeang; Femmy Indriany Dalimunthe; Muhammad Halfi Indra Syahputra (Pusat Riset dan Inovasi Nasional, 2022)
The objectives of this thesis include: Analyzing the development of the tourist village of Pematang Johar, Deli Serdang Regency, analyzing the inhibiting and supporting factors that influence the development plan of the Tourism Village of Pematang Johar, Deli Serdang Regency and formulating and formulating a tourism development strategy in developing the Tourism Village of Pematang Johar, Deli Serdang Regency. To answer the first objective using the 4A theory analysis ( attraction, accessibility, amenity and ancillary ), to answer the second objective using the IFAS ( Internal Strategy Factors Analysis Summary) and EFAS ( External Strategy Factors Analysis Summary) methods, to answer the third objective is to combine the results 4A analysis and the results of the IFAS and EFAS calculations contained in the IE Matrix. The attractions in Pematang Johar Village are rice harvesting activities, rice field batik activities, enjoying food and drinks in huts in the middle of the rice fields, adequate accessibility, amenities, namely health facilities, security facilities, existing worship facilities and good, as well as ancillary or additional services through the existence of POKDARWIS (Tourism Awareness Group) and BUMDes which assist in the development of Pematang Johar village. From the results of the calculation of IFAS with a total value of 2.7 and EFAS with a total value of 3.14, then based on the results of the Internal and External (IE) matrix analysis shows that the development of the Pematang Johar tourist village is in cell II, namely growing and fostering, the strategy taken is to implement an intensive strategy, namely through market penetration, market development and product development.